2016
DOI: 10.1002/adom.201600296
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion Nanocrystal‐Doped Glass: A New Paradigm for Photonic Materials

Abstract: The integration of novel luminescent nanomaterials into glassy matrix can lead to new hybrid materials and photonic devices with promising material performance and device functions. Lanthanide‐containing upconversion nanocrystals have become unique candidates for sensing, bioimaging, photon energy management, volumetric displays, and other photonic applications. Here, a versatile direct‐doping approach is developed to integrate bright upconversion nanocrystals in tellurite glass with tailored nanoscale propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 68 publications
0
53
0
Order By: Relevance
“…First, a host glass in which the nanocrystals can be dispersed without being decomposed, needs to be identied. As explained in, 20 two parameters need to be optimized when preparing a nanocrystals-containing glass using the direct particles doping method: the doping temperature (T doping ) at which the nanocrystals are added in the glass batch and the dwell time before quenching the glass aer adding the nanocrystals. The doping temperature should be lower than the nanocrystals' dissolution points, which was reported to be 750 C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a host glass in which the nanocrystals can be dispersed without being decomposed, needs to be identied. As explained in, 20 two parameters need to be optimized when preparing a nanocrystals-containing glass using the direct particles doping method: the doping temperature (T doping ) at which the nanocrystals are added in the glass batch and the dwell time before quenching the glass aer adding the nanocrystals. The doping temperature should be lower than the nanocrystals' dissolution points, which was reported to be 750 C.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low dissolution point (750 C) of the nanocrystals, the glasses could be only obtained using direct particles doping method. 20 The concept of this method is based on using glass matrices with lower melting temperatures than those of the admixed nanoparticles. Using this method, we found that it is possible to increase the upconversion intensity from the NaYF 4 :Er 3+ ,Yb 3+ nanocrystals containing phosphate glasses by replacing Na 2 O by NaF in the glass matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an alternative approach, the direct doping of NCs into tellurite-based glass melts, was developed [84][85][86][87]. This approach comprises a two-temperature melting procedure.…”
Section: Nanoparticle-doped Glasses and Fibersmentioning
confidence: 99%
“…Building on the success in doping ND into TZN glass, LiYF4:Yb,Er UPNCs were successfully doped into TZN glass and fiber [87]. As for the ND doping, fine-tuning of the doping temperature and time was critical to balance NC dissolution and dispersion (Figure 4a).…”
Section: Nanoparticle-doped Glasses and Fibersmentioning
confidence: 99%
“…The integration of novel luminescent nanometer materials into glassy matrix can bring about new and promising optical hybrid materials and photonic devices in recent years [1]. Great enhancement of optical emission efficiency was realized in fluorosilicate glasses by the growth of the lanthanide doped fluoride nanocrystals embedded in the glass matrix [2].…”
Section: Introductionmentioning
confidence: 99%